Palais, forteresses et pyramides. Patrimoine matériel et immatériel de la justice. Quelle histoire pour l’organisation pénale napoléonienne en France ? - Frédéric Chauvaud (Criminocorpus)
The courthouses, sometimes nicknamed the Temples of Justice, preserved, destroyed and renovated, have a history in which the Napoleonic period occupies a decisive place, even if few achievements have seen “the light of day”. But the judicial heritage includes both the material elements such as buildings and statues, but also the intangible elements such as projects, the main ideas and above all the imaginary of a judicial organization that seemed unsurpassable. Indeed, even under the Third Republic, in the speeches at the beginning of the school year, the highest magistrates affirmed that the Napoleonic judicial institution embodied "the best possible justice". However, it must be admitted that historiography has, if not deserted, at least neglected the study of the Napoleonic judicial organization or even of the prison. Indeed, the Napoleonic episode is not studied as such but as a moment in a larger whole. And yet, in existing works, "problematic points" are sketched out to explain this collective lack of interest in the Napoleonic model, which succeeds in presenting itself as perfect and imposing itself on social imaginaries.